Using metamodels and workflows in a software maintenance environment - Piattini Velthuis, Mario (2001)
The objective of Software Engineering Environments (SEE) is to allow the integrated and automatic management and control of a specific process or group of processes of the software (ISO/IEC, 2000). In broader terms, the MANTIS project aims to define and construct an integral environment for the management of Software Maintenance Process (SMP). Due to the large number of different aspects that have to be considered, we have defined an architecture with 4 conceptual levels. Each of these levels incorporates concepts at a specific level of abstraction and generality. We present a proposal of a metamodel for the SMP based on the ontology formulated by Kitchenham et al.(1999) and in the Workflow Reference Model of the Workflow Management Coalition (WFMC, 1995). In so doing our aim is to incorporate in the said ontology, the aspects of process enaction that the workflow technology resolves in what we consider to be a satisfactory fashion.